Hollow Y zeolite and synthesis method thereof

By treating Y zeolite under organic amine steam conditions and performing secondary reactions with inorganic alkali, aluminum source and silicon source, the problem of difficulty in synthesizing hollow Y zeolite in the prior art was solved, and a suitable drug carrier and catalytic material was prepared Hollow Y zeolite achieves the effect of drug sustained release and catalytic application.

CN119320143AActive Publication Date: 2025-01-17CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202310867534.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-15
Publication Date
2025-01-17
Estimated Expiration
2043-07-15

AI Technical Summary

Technical Problem

It is difficult to synthesize hollow Y zeolites in the prior art, and the existing methods are not suitable for the preparation of Y zeolites, resulting in the inability to form a hollow structure.

Method used

Y zeolite is treated under organic amine steam conditions, and a hollow NaY or HY zeolite is formed through secondary reaction with inorganic alkali, aluminum source, silicon source and other materials. The crystal structure is maintained intact by organic amines, and the aluminum elements are rearranged to form hollow structure.

Benefits of technology

Hollow Y zeolite with a single crystal particle was successfully prepared, suitable for drug carriers and sustained-release agents, which increased the molecular load and sustained-release time, and had wide application prospects as adsorbents and catalytic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320143A_ABST
    Figure CN119320143A_ABST
Patent Text Reader

Abstract

The present invention discloses a hollow Y zeolite and a synthesis method thereof, the zeolite crystal form is a Y zeolite structure, the zeolite is represented as a single crystal particle hollow structure crystal through a transmission electron microscope, and the center part of the crystal is a cavity. The synthesis method of the hollow Y zeolite comprises the following steps: treating Y zeolite in the presence of organic amine steam, washing, separating and drying to obtain a material after treatment, and further reacting the material with inorganic alkali, an aluminum source, a silicon source and water to obtain the hollow NaY zeolite. The problem that hollow Y zeolite cannot be synthesized in the prior art is solved, and the synthesis method is simple and easy to implement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a zeolite material and a preparation method thereof, in particular to a Y zeolite and a synthesis method thereof. Background Art

[0002] Hollow zeolite molecular sieves have unique physical and chemical properties and show broad application prospects in shape-selective adsorbents, catalysts, drug sustained-release agents and microreactors. The development of hollow zeolite molecular sieves and new synthesis technologies is of great significance.

[0003] Patent CN105712374A discloses a method for preparing a hollow USY molecular sieve, comprising the following steps: (1) preparing a directing agent; (2) preparing an aluminum source, water, sodium hydroxide and water into a mixed solution, then adding a low silicon-aluminum ratio NaY type molecular sieve and the directing agent obtained in step (1), stirring evenly, crystallizing the gel at a constant temperature of 90 to 120° C. for 12 to 72 hours, and then cooling, washing, filtering and drying to obtain a YY composite molecular sieve; (3) exchanging the YY composite molecular sieve prepared in step (2) with ammonium; (4) treating the YY composite molecular sieve after the ammonium exchange in step (3) under hydrothermal conditions; (5) washing the composite molecular sieve obtained by the hydrothermal treatment in step (4) under acidic conditions to obtain a hollow USY molecular sieve. The method first uses a low silicon-aluminum ratio NaY type molecular sieve as a core to prepare an isomorphous composite molecular sieve, and then utilizes the difference in hydrothermal stability between the low silicon-aluminum ratio NaY core and the high silicon shell of the prepared composite molecular sieve. During the hydrothermal treatment of the molecular sieve, the low silicon-aluminum ratio core is hydrothermally treated to become an amorphous structure, while the shell high silicon Y type molecular sieve still maintains its crystalline structure after hydrothermal treatment. Then, the sodium oxide and amorphous aluminum oxide in the molecular sieve are successfully washed away through an acid washing process, thereby achieving the purpose of modifying the Y type molecular sieve and preparing a hollow USY molecular sieve.

[0004] Patent CN102491366A discloses a method for preparing a hollow ZSM-5 nano zeolite, which comprises the following steps: mixing a monodispersed ZSM-5 nano zeolite having a silicon-aluminum molar ratio SiO2 / Al2O3 of more than 20 and a particle size of 100-400nm with an alkaline aqueous solution having a concentration of 0.05-0.5mol / L; wherein the alkaline substance is selected from a mixture of a quaternary ammonium salt and sodium hydroxide in a molar ratio of 1:1, a mixture of a quaternary ammonium salt and potassium hydroxide in a molar ratio of 1:1, n-butylamine and a quaternary ammonium base; stirring for 10h-200h at 80-200°C, and separating. The present invention forms a regular cavity structure, which is conducive to the transfer of reactants and products, has high crystallinity, is simple in method, low in cost, high in yield, and can be mass-produced. Hollow ZSM-5 nano zeolites with different silicon-aluminum ratios can be obtained by using different matrixes or different processing conditions. The size of the hollow ZSM-5 nanozeolite cavities can be adjusted by changing the processing conditions.

[0005] CN104591220A provides a hollow beta zeolite and a preparation method thereof, wherein water, an inorganic base, an aluminum source and the beta zeolite are first mixed and stirred in sequence; then the mixture is placed in a closed reactor and treated at a constant temperature for a certain period of time to obtain the hollow beta zeolite. The hollow beta zeolite prepared by the present invention has a crystal structure of beta zeolite, and the center of the crystal is hollow, and is suitable as an adsorbent for separating gas and liquid mixtures, and can also be used as a catalyst carrier or an acidic catalyst component, and is particularly suitable for use as a special functional material.

[0006] CN1480401A discloses a liquid-solid phase preparation method for zeolite hollow microspheres. The invention uses mesoporous silica microspheres as templates and silicon sources, assembles nano-zeolite crystal seeds onto the surface of silica microspheres under electrostatic action, and then prepares zeolite hollow microspheres through secondary growth in a silicon-free solution through liquid-solid phase treatment technology. Summary of the invention

[0007] In view of the deficiencies in the prior art, the main purpose of the present invention is to provide a hollow Y zeolite and a synthesis method thereof, which solves the problem that it is difficult to synthesize hollow Y zeolite in the prior art, and the synthesis method is simple and easy.

[0008] The first aspect of the present invention provides a hollow Y zeolite having the following characteristics: the zeolite crystal form is a Y zeolite structure, characterized by a transmission electron microscope as a single crystal particle with a hollow structure, and the center of the crystal is a cavity.

[0009] Furthermore, the particle diameter of the hollow Y zeolite crystals is 80 to 650 nm, preferably 100 to 600 nm.

[0010] Furthermore, the shell thickness of the hollow Y zeolite is 20 to 350 nm, preferably 30 to 300 nm.

[0011] Furthermore, the specific surface area of ​​hollow Y zeolite is 280-730 m 2 / g, preferably 300 to 700 m 2 / g; pore volume is 0.09~0.31cm 3 / g, preferably 0.1 to 0.3 cm 3 / g.

[0012] Furthermore, the acid content of the hollow Y zeolite is 0.07 to 0.27 mmol / g, preferably 0.08 to 0.25 mmol / g.

[0013] Furthermore, the hollow Y zeolite has an oxide silicon-aluminum ratio of 3 to 7, preferably 3.2 to 6.5.

[0014] The second aspect of the present invention provides a method for synthesizing hollow Y zeolite, the method comprising the following steps:

[0015] (1) treating Y zeolite in the presence of organic amine vapor, and washing, separating and drying to obtain material A after the treatment;

[0016] (2) The material A obtained in step (1), an inorganic base, an aluminum source, a silicon source and water are uniformly mixed, and after the reaction, the hollow NaY zeolite is obtained by washing, separating, drying and roasting.

[0017] The third aspect of the present invention provides a method for synthesizing hollow Y zeolite, the method comprising the following steps:

[0018] (1) treating Y zeolite in the presence of organic amine vapor, and washing, separating and drying to obtain material A after the treatment;

[0019] (2) uniformly mixing the material A obtained in step (1), an inorganic base, an aluminum source, a silicon source, and water, and washing, separating, and drying after the reaction to obtain material B;

[0020] (3) Material B is subjected to ammonium exchange treatment, and finally hollow HY zeolite is obtained after separation, drying and calcination.

[0021] Furthermore, in the synthesis method of hollow Y zeolite, as a specific embodiment, the organic amine in step (1) is at least one of ethylenediamine, propylenediamine, butylenediamine, n-propylamine, isopropylamine, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, and tetrabutylammonium hydroxide, preferably at least one of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, and tetrabutylammonium hydroxide.

[0022] Furthermore, in the synthesis method of hollow Y zeolite, as a specific embodiment, the treatment in step (1) is a gas-solid two-phase reaction, and the Y zeolite is treated in the presence of organic amine vapor. More specifically, it can be achieved in the following manner: a support is provided in the reactor, the Y zeolite is placed on the support, and a mixture of organic amine and water is added to the lower part of the reactor support; the Y zeolite is not in direct contact with the liquid (the mixture of organic amine and water); further, the mass ratio of the Y zeolite, the organic amine, and the water is 8-25:8-25:100, preferably 10-20:10-20:100.

[0023] Furthermore, in the synthesis method of hollow Y zeolite, as a specific embodiment, the treatment temperature in step (1) is 280-530°C, preferably 300-500°C, and the treatment time is 5-12h, preferably 6-10h.

[0024] Furthermore, in the synthesis method of hollow Y zeolite, as a specific implementation, the washing in step (1) is to wash with deionized water until the filtrate is neutral, and usually multiple washings are required.

[0025] Furthermore, in the synthesis method of hollow Y zeolite, as a specific implementation, the separation in step (1) is solid-liquid separation, and any of the existing methods for separating solid-liquid two-phase materials can be used, specifically, it can be carried out by filtration, usually including multiple filtrations, generally 1 to 10 times.

[0026] Furthermore, in the synthesis method of hollow Y zeolite, as a specific implementation, the drying conditions in step (1) are as follows: the drying temperature is 100 to 140° C.; and the drying time is 5 to 15 hours.

[0027] Furthermore, in the method for synthesizing hollow Y zeolite, as a specific embodiment, the Y zeolite in step (1) is selected from commercial Y zeolite in the art, or synthesized by an existing method for synthesizing Y zeolite. In a further preferred case, the particle diameter of the Y zeolite crystal is 80 to 650 nm, and the specific surface area is 260 to 760 m 2 / g, pore volume is 0.09~0.32cm 3 / g, the acid content is 0.06~0.27mmol / g, and the oxide silicon-aluminum ratio is 3~7.

[0028] Furthermore, in the method for synthesizing hollow Y zeolite, as a specific implementation, the inorganic base in step (2) can be one or more of sodium hydroxide, potassium hydroxide, and lithium hydroxide.

[0029] Furthermore, in the method for synthesizing hollow Y zeolite, as a specific embodiment, the aluminum source in step (2) can be one or more of sodium aluminate, aluminum sulfate, aluminum chloride, and aluminum nitrate.

[0030] Furthermore, in the method for synthesizing hollow Y zeolite, as a specific implementation, the silicon source in step (2) is one or more of white carbon black, silica gel, and silica sol.

[0031] Furthermore, in the synthesis method of hollow Y zeolite, as a specific embodiment, the mass ratio of inorganic base, aluminum source, silicon source, material A, and water is 0.8-2.5:0.4-1.8:2.5-6:8-25:100, preferably 1-2:0.5-1.5:3-5:10-20:100.

[0032] Furthermore, in the synthesis method of hollow Y zeolite, as a specific embodiment, the reaction conditions in step (2) are as follows: the reaction temperature is 70-150°C, preferably 80-120°C, and the treatment time is 15-35h, preferably 20-30h.

[0033] Furthermore, in the synthesis method of hollow Y zeolite, as a specific implementation, the washing in step (2) is washing with deionized water until the filtrate is neutral, and usually multiple washings are required.

[0034] Furthermore, in the synthesis method of hollow Y zeolite, as a specific implementation, the separation in step (2) is solid-liquid separation, and any of the existing methods for separating solid-liquid two-phase materials can be used, specifically, it can be carried out by filtration, usually including multiple filtrations, generally 1 to 10 times.

[0035] Furthermore, in the synthesis method of hollow Y zeolite, as a specific implementation, the drying temperature in step (2) is 80 to 150° C., and the drying time is 1 to 20 hours.

[0036] Furthermore, in the synthesis method of hollow Y zeolite, as a specific implementation, the calcination temperature in step (2) is 400-700° C., and the calcination time is 1-20 h; the calcination is carried out in air or oxygen atmosphere.

[0037] Furthermore, in the method for synthesizing hollow Y zeolite, as a specific embodiment, the ammonium exchange treatment in step (3) is performed at least once, preferably 3 to 5 times.

[0038] Furthermore, in the synthesis method of hollow Y zeolite, as a specific implementation, the ammonium exchange treatment in step (3) can adopt any of the existing ammonium exchange methods in the art.

[0039] Furthermore, in the synthesis method of hollow Y zeolite, as a specific embodiment, the ammonium exchange treatment in step (3) is to mix material B, ammonium salt and water for ion exchange treatment, wherein the mass ratio of material B, ammonium salt and water is 8-25:8-25:100, preferably 10-20:10-20:100.

[0040] Furthermore, in the synthesis method of hollow Y zeolite, as a specific embodiment, the ammonium salt can be one or more of ammonium nitrate and ammonium chloride, preferably ammonium nitrate.

[0041] Furthermore, in the synthesis method of hollow Y zeolite, as a specific embodiment, the ion exchange treatment temperature is 70-100° C., preferably 80-90° C., and the ion exchange treatment time is 1-5 h, preferably 2-4 h.

[0042] Furthermore, in the synthesis method of hollow Y zeolite, as a specific implementation, the washing in step (3) is to wash with deionized water until the filtrate is neutral, and usually multiple washings are required.

[0043] Furthermore, in the synthesis method of hollow Y zeolite, as a specific implementation, the separation in step (3) is solid-liquid separation, and any of the existing methods for separating solid-liquid two-phase materials can be used, specifically, it can be carried out by filtration, usually including multiple filtrations, generally 1 to 10 times.

[0044] Furthermore, in the synthesis method of hollow Y zeolite, as a specific implementation, the drying temperature in step (3) is 80 to 150° C., and the drying time is 1 to 20 hours.

[0045] In the method of the present invention, the calcination temperature in step (3) is 400-600° C., and the calcination time is 1-10 hours. The calcination needs to be carried out under oxygen-containing atmosphere conditions, such as air or oxygen.

[0046] The invention also provides a hollow Y zeolite obtained by the synthesis method.

[0047] The hollow Y zeolite provided by the present invention can be used as a carrier of molecules such as drugs, and can achieve sustained release of loaded molecules.

[0048] The hollow Y zeolite provided by the present invention can also be used as an adsorbent.

[0049] The hollow Y zeolite provided by the present invention can also be used as a catalytic material.

[0050] Compared with the prior art, the Y zeolite and the synthesis method thereof provided by the present invention have the following advantages:

[0051] Although the prior art discloses a variety of methods for preparing hollow materials, the applicant discovered during the research process that the existing methods for preparing hollow zeolite materials are not suitable for the preparation of hollow Y zeolite. After analysis, it is believed that the physical and chemical properties of zeolite are very different due to the different crystal structures of zeolites. Just as the synthesis methods of different types of zeolites are not universal, the synthesis methods of hollow zeolites are not universal between different types of zeolites, and different hollow structure zeolites cannot be obtained by directly replacing the types of raw materials. For example, conventional zeolite is treated with inorganic bases to produce a mesoporous structure in the zeolite crystal to obtain a mesoporous zeolite; however, CN104591220A can prepare hollow Beta zeolite under the joint action of inorganic bases and aluminum sources. Because Y zeolite has special properties, the existing method cannot process conventional Y zeolite to obtain hollow structure Y zeolite.

[0052] In the Y zeolite synthesis method provided by the present invention, the Y zeolite is first contacted with organic amine vapor for high temperature treatment. During the treatment process, the silicon and aluminum elements in the zeolite crystal are rearranged. It may be that the aluminum element migrates to the outside of the crystal, causing the aluminum content of the outside of the crystal to increase, while the aluminum content of the inside is reduced, causing the aluminum element to form a gradient distribution in the crystal, which is conducive to the formation of a hollow structure. In addition, in the presence of the organic amine, the crystal structure remains relatively intact and will not be seriously damaged.

[0053] In the Y zeolite synthesis method provided by the present invention, the modified Y zeolite is mixed with other raw materials (inorganic alkali, aluminum source, silicon source) to undergo a secondary crystallization reaction. At the same time, the material ratio of other raw materials is quite different from the existing raw material ratio for preparing Y zeolite, and is not within the effective range of the current conventional hydrothermal synthesis reaction material ratio. The secondary reaction in this application is different from the hydrothermal synthesis reaction of the existing zeolite. During the secondary reaction process in this application, the inorganic alkali, aluminum source, and silicon source react with the treated Y zeolite, and the aluminum element enters the outside of the zeolite crystal, while the inside of the zeolite crystal undergoes a dissolution reaction, thereby forming a hollow form. In this process, the silicon source will not basically enter the zeolite crystal skeleton. After research, it is analyzed that in the synthesis method of the present invention, the silicon source only plays a role in stabilizing the system. In the absence of a silicon source, the zeolite cannot be effectively converted into a hollow structure. And the HY zeolite material synthesized by the present invention has an increased acid content compared to the original material, and can load more molecules in the process of loading and sustained release of molecules such as drugs, and can also increase the time of sustained release.

[0054] In summary, the Y zeolite synthesis method provided by the present invention provides a new method for preparing hollow Y zeolite by combining two means: treating Y zeolite with organic amine steam and subjecting the treated Y zeolite to a secondary reaction with an inorganic base, an aluminum source, a silicon source and water, and obtains a hollow Y zeolite with a completely new structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 This is a transmission electron microscope photograph of the sample obtained in Example 1.

[0056] Figure 2 This is a transmission electron microscope photograph of the sample obtained in Comparative Example 1.

[0057] Figure 3 This is the XRD spectrum of the sample obtained in Example 1.

[0058] Figure 4 The XRD spectrum of the sample obtained for Comparative Example 1. DETAILED DESCRIPTION

[0059] The technical solution and technical effects of the present invention are further explained below through the accompanying drawings and in combination with specific implementations, but are not limited to the following implementations.

[0060] In this paper, the pore structure of zeolite materials was characterized by N2 adsorption-desorption and tested by a physical adsorption instrument from Micromeritics, USA. Before the test, the samples were vacuum treated at 300℃ for more than 4h. The specific surface area, pore size and other parameters were calculated according to the BET and BJH formulas.

[0061] In this paper, the phase structure and crystallinity of zeolite materials were characterized by X-ray diffraction, and the test was carried out using a Japanese Rigaku D / max2500 X-ray diffractometer with Cu target, Kα radiation source, graphite monochromator, tube voltage 40 kV, tube current 80 mA, scanning range 5°~40°, step size 0.1°, and scanning speed 1° / min.

[0062] In this paper, the acid content of the zeolite material was measured by ammonia temperature-programmed desorption. The ammonia temperature-programmed desorption test was performed using an AutoChem II 2920 chemical adsorption instrument manufactured by Micromeritics, USA. First, under the protection of helium, the temperature was raised to 550°C at a rate of 10°C / min and maintained for 1 hour; then the temperature was lowered to room temperature (25°C) at a rate of 10°C / min, replaced with ammonia and adsorbed for 1 hour; then replaced with helium and heated to 600°C at a rate of 10°C / min.

[0063] In this paper, the crystal morphology of the zeolite material was characterized by transmission electron microscopy, using a high-resolution transmission electron microscope (TEM) from JEOL, Japan. The instrument model was JEM-2200FS field emission ultra-high resolution transmission electron microscope, with an acceleration voltage of 200KV and a point resolution of 0.19nm.

[0064] In this article, the chemical reagents used are all analytically pure chemical reagents and can be obtained by purchasing commercial products.

[0065] In this paper, the Y zeolite crystal size is about 200nm, the oxide silicon-aluminum ratio is 5.23, and the specific surface area is 697m 2 / g, the acid amount is 0.176mmol / g.

[0066] Example 1

[0067] (1) According to the mass ratio of Y zeolite, tetraethylammonium hydroxide and water of 15:13:100, Y zeolite is placed on a support in a reactor, and water and tetraethylammonium hydroxide are added to the bottom of the reactor. Then the reaction is carried out at 400°C for 8 hours. After the reaction is completed, the obtained solid is washed with water and filtered for multiple times, and then dried at 120°C for 10 hours to obtain material A.

[0068] (2) Then, sodium hydroxide, aluminum nitrate, white carbon black, material A, and deionized water were added in the proportion (mass ratio of inorganic base, aluminum source, silicon source, material A, and water = 1.7:1.1:4:12:100) and mixed evenly. Then, the mixture was placed in a closed reactor and reacted at 100°C for 25 hours. After the reaction, the obtained solid sample was filtered several times, and then dried at 120°C for 10 hours to obtain material B.

[0069] (3) Then, ammonium nitrate and deionized water were added to material B in the ratio (mass ratio of ammonium nitrate, material B, and water = 16:15:100) and mixed evenly, followed by treatment at 85°C for 3 hours, and the treatment was repeated 3 times.

[0070] (4) The solid sample was filtered several times, dried at 120°C for 10 h, and finally calcined in air at 500°C for 10 h. The obtained sample was numbered C1.

[0071] The crystal structure of the prepared sample belongs to Y zeolite, and its crystal morphology is a hollow shell structure.

[0072] Example 2

[0073] (1) According to the mass ratio of Y zeolite, organic matter and water of 10:10:100, Y zeolite is placed on a support in a reactor, and water and tetraethylammonium hydroxide are added to the bottom of the reactor. Then the reaction is carried out at 300°C for 10 hours. After the reaction is completed, the obtained solid sample is washed with water and filtered for multiple times, and then dried at 120°C for 10 hours to obtain material A.

[0074] (2) Then, sodium hydroxide, aluminum nitrate, white carbon black, material A, and deionized water were added in the proportion (mass ratio of inorganic base, aluminum source, silicon source, material A, and water = 1:0.5:3:10:100) and mixed evenly. Then, the mixture was placed in a closed reactor and reacted at 80°C for 20 hours. After the reaction, the obtained solid sample was filtered several times, and then dried at 120°C for 10 hours to obtain material B.

[0075] (3) Then, add ammonium nitrate and deionized water to material B according to the ratio (mass ratio of ammonium nitrate, material B, and water = 10:10:100) and mix well. Then treat at 90°C for 2 hours. Repeat the treatment 3 times.

[0076] (4) The solid sample was filtered several times, dried at 120°C for 10 h, and finally calcined in air at 500°C for 10 h. The obtained sample was numbered C2.

[0077] The crystal structure of the prepared sample belongs to Y zeolite, and its crystal morphology is a hollow shell structure.

[0078] Example 3

[0079] (1) Y zeolite is placed on a support in a reactor according to a mass ratio of Y zeolite, tetrapropylammonium hydroxide and water of 20:20:100, and water and tetrapropylammonium hydroxide are added to the bottom of the reactor. Then, the reaction is carried out at 500°C for 6 hours. After the reaction is completed, the obtained solid sample is washed with water and filtered for multiple times, and then dried at 120°C for 10 hours to obtain material A.

[0080] (2) Then, sodium hydroxide, aluminum nitrate, white carbon black, material A, and deionized water were added in the proportion (mass ratio of inorganic base, aluminum source, silicon source, material A, and water = 2:1.5:5:20:100) and mixed evenly. Then, the mixture was placed in a closed reactor and reacted at 120°C for 30 hours. After the reaction, the obtained solid sample was filtered several times, and then dried at 120°C for 10 hours to obtain material B.

[0081] (3) Then add ammonium nitrate and deionized water to material B according to the ratio (mass ratio of ammonium nitrate, material B, water = 20:20:100) and mix well. Then treat at 80°C for 4 hours. Repeat the treatment 3 times.

[0082] (4) The solid sample was filtered several times, dried at 120°C for 10 h, and finally calcined in air at 500°C for 10 h. The obtained sample was numbered C3.

[0083] The crystal structure of the prepared sample belongs to Y zeolite, and its crystal morphology is a hollow shell structure.

[0084] Example 4

[0085] (1) Y zeolite is placed on a support in a reactor according to a mass ratio of Y zeolite, tetrabutylammonium hydroxide and water of 13.5:12.3:100, and water and tetrabutylammonium hydroxide are added to the bottom of the reactor. Then, the reaction is carried out at 420°C for 8 hours. After the reaction is completed, the obtained solid sample is washed with water and filtered for multiple times, and then dried at 120°C for 10 hours to obtain material A.

[0086] (2) Then, sodium hydroxide, aluminum chloride, white carbon black, material A, and deionized water were added in the proportion (mass ratio of inorganic base, aluminum source, silicon source, material A, and water = 1.2:1.1:4.2:12.5:100) and mixed evenly. Then, the mixture was placed in a closed reactor and reacted at 112°C for 22 hours. After the reaction, the obtained solid sample was filtered several times, and then dried at 120°C for 10 hours to obtain material B.

[0087] (3) Then, add ammonium nitrate and deionized water to material B according to the ratio (mass ratio of ammonium nitrate, material B, and water = 16.2:15.3:100) and mix well. Then treat at 83°C for 3 hours. Repeat the treatment 3 times.

[0088] (4) The solid sample was filtered several times, dried at 120°C for 10 h, and finally calcined in air at 500°C for 10 h. The obtained sample was numbered C4.

[0089] The crystal structure of the prepared sample belongs to Y zeolite, and its crystal morphology is a hollow shell structure.

[0090] Example 5

[0091] (1) According to the mass ratio of Y zeolite, tetraethylammonium hydroxide and water of 11.5:17.3:100, Y zeolite is placed on a support in a reactor, and water and tetraethylammonium hydroxide are added to the bottom of the reactor. Then the reaction is carried out at 430°C for 7 hours. After the reaction is completed, the obtained solid sample is washed with water and filtered for multiple times, and then dried at 120°C for 10 hours to obtain material A.

[0092] (2) Then, sodium hydroxide, aluminum sulfate, white carbon black, material A, and deionized water were added in the proportion (mass ratio of inorganic base, aluminum source, silicon source, material A, and water = 1.2:1.3:4.5:13.5:100) and mixed evenly. Then, the mixture was placed in a closed reactor and reacted at 90°C for 25 hours. After the reaction, the obtained solid sample was filtered several times, and then dried at 120°C for 10 hours to obtain material B.

[0093] (3) Then, add ammonium nitrate and deionized water to material B according to the ratio (mass ratio of ammonium nitrate, material B, and water = 16.5:11:100) and mix well. Then treat at 85°C for 3 hours. Repeat the treatment 3 times.

[0094] (4) The solid sample was filtered several times, dried at 120°C for 10 h, and finally calcined in air at 500°C for 10 h. The obtained sample was numbered C5.

[0095] The crystal structure of the prepared sample belongs to Y zeolite, and its crystal morphology is a hollow shell structure.

[0096] Comparative Example 1

[0097] No treatment was performed on the Y zeolite.

[0098] (1) Then, Y zeolite, sodium hydroxide, aluminum nitrate, white carbon black and deionized water are mixed evenly according to the ratio (mass ratio of inorganic base, aluminum source, silicon source, Y zeolite and water = 1.7:1.1:4:12:100). Then, the mixture is placed in a closed reactor and reacted at 100°C for 25 hours. After the reaction, the obtained solid sample is filtered several times and then dried at 120°C for 10 hours to obtain material B.

[0099] (2) Then add ammonium nitrate and deionized water to material B according to the ratio (mass ratio of ammonium nitrate, material B, water = 16:15:100) and mix well. Then treat at 85°C for 3 hours. Repeat the treatment 3 times.

[0100] (3) The solid sample was filtered several times, dried at 120°C for 10 h, and finally calcined in air at 500°C for 10 h. The obtained sample was numbered C6.

[0101] The crystal structure of the prepared sample belongs to Y zeolite, but it is not a hollow structure, which indicates that step (1) of the present invention is an indispensable step.

[0102] Comparative Example 2

[0103] (1) According to the mass ratio of Y zeolite, tetraethylammonium hydroxide and water of 15:13:100, Y zeolite is placed on a support in a reactor, and water and tetraethylammonium hydroxide are added to the bottom of the reactor. Then the reaction is carried out at 400°C for 8 hours. After the reaction is completed, the obtained solid is washed with water and filtered for multiple times, and then dried at 120°C for 10 hours to obtain material A.

[0104] (2) Then, sodium hydroxide, white carbon black, material A, and deionized water were added in the proportion (mass ratio of inorganic base, silicon source, material A, and water = 1.7:4:12:100) and mixed evenly. Then, the mixture was placed in a closed reactor and reacted at 100°C for 25 hours. After the reaction, the obtained solid sample was filtered several times, and then dried at 120°C for 10 hours to obtain material B.

[0105] (3) Then add ammonium nitrate and deionized water to material B according to the ratio (mass ratio of ammonium nitrate, material B, water = 16:15:100) and mix well. Then treat at 85°C for 3 hours. Repeat the treatment 3 times.

[0106] (4) The solid sample was filtered several times, dried at 120°C for 10 h, and finally calcined in air at 500°C for 10 h. The obtained sample was numbered C7.

[0107] The crystal structure of the prepared sample belongs to Y zeolite, but it is not a hollow structure, which indicates that the aluminum source in step (3) of the present invention is indispensable.

[0108] Comparative Example 3

[0109] (1) According to the mass ratio of Y zeolite, tetraethylammonium hydroxide and water of 15:13:100, Y zeolite is placed on a support in a reactor, and water and tetraethylammonium hydroxide are added to the bottom of the reactor. Then the reaction is carried out at 400°C for 8 hours. After the reaction is completed, the obtained solid is washed with water and filtered for multiple times, and then dried at 120°C for 10 hours to obtain material A.

[0110] (2) Then, sodium hydroxide, aluminum nitrate, material A, and deionized water were added in the ratio (mass ratio of inorganic base, aluminum source, material A, and water = 1.7:1.1:12:100) and mixed evenly. Then, the mixture was placed in a closed reactor and reacted at 100°C for 25 hours. After the reaction, the obtained solid sample was filtered several times, and then dried at 120°C for 10 hours to obtain material B.

[0111] (3) Then add ammonium nitrate and deionized water to material B according to the ratio (mass ratio of ammonium nitrate, material B, water = 16:15:100) and mix well. Then treat at 85°C for 3 hours. Repeat the treatment 3 times.

[0112] (4) The solid sample was filtered several times, dried at 120°C for 10 h, and finally calcined in air at 500°C for 10 h. The obtained sample was numbered C8.

[0113] The crystal structure of the prepared sample belongs to Y zeolite, but it is not a hollow structure, which indicates that the silicon source in step (3) of the present invention is indispensable.

[0114] Comparative Example 4

[0115] (1) According to the mass ratio of Y zeolite, tetraethylammonium hydroxide and water of 15:13:100, Y zeolite is placed on a support in a reactor, and water and tetraethylammonium hydroxide are added to the bottom of the reactor. Then the reaction is carried out at 400°C for 8 hours. After the reaction is completed, the obtained solid is washed with water and filtered for multiple times, and then dried at 120°C for 10 hours to obtain material A.

[0116] (2) Then, sodium hydroxide, aluminum nitrate, white carbon black, material A, and deionized water were added in the proportion (mass ratio of inorganic base, aluminum source, silicon source, material A, and water = 3.2:3:16:1.6:100) and mixed evenly. Then, the mixture was placed in a closed reactor and reacted at 100°C for 50 hours. After the reaction, the obtained solid sample was filtered several times, and then dried at 120°C for 10 hours to obtain material B.

[0117] (3) Then, ammonium nitrate and deionized water were added to material B in the ratio (mass ratio of ammonium nitrate, material B, and water = 16:15:100) and mixed evenly, followed by treatment at 85°C for 3 hours, and the treatment was repeated 3 times.

[0118] (4) The solid sample was filtered several times, dried at 120°C for 10 h, and finally calcined in air at 500°C for 10 h. The obtained sample was numbered C9.

[0119] The crystal structure of the prepared sample belongs to Y zeolite, which is a conventional form of Y zeolite.

[0120] Comparative Example 5

[0121] (1) According to the mass ratio of Y zeolite, tetraethylammonium hydroxide and water of 15:13:100, Y zeolite is placed on a support in a reactor, and water and tetraethylammonium hydroxide are added to the bottom of the reactor. Then the reaction is carried out at 100°C for 8 hours. After the reaction is completed, the obtained solid is washed with water and filtered for multiple times, and then dried at 120°C for 10 hours to obtain material A.

[0122] (2) Then, sodium hydroxide, aluminum nitrate, white carbon black, material A, and deionized water were added in the proportion (mass ratio of inorganic base, aluminum source, silicon source, material A, and water = 1.7:1.1:4:12:100) and mixed evenly. Then, the mixture was placed in a closed reactor and reacted at 100°C for 25 hours. After the reaction, the obtained solid sample was filtered several times, and then dried at 120°C for 10 hours to obtain material B.

[0123] (3) Then, ammonium nitrate and deionized water were added to material B in the ratio (mass ratio of ammonium nitrate, material B, and water = 16:15:100) and mixed evenly, followed by treatment at 85°C for 3 hours, and the treatment was repeated 3 times.

[0124] (4) The solid sample was filtered several times, dried at 120°C for 10 h, and finally calcined in air at 500°C for 10 h. The obtained sample was numbered C10.

[0125] The crystal structure of the prepared sample belongs to Y zeolite, which is a conventional form of Y zeolite.

[0126] Comparative Example 6

[0127] (1) According to the mass ratio of Y zeolite, tetraethylammonium hydroxide and water of 15:13:100, Y zeolite is placed on a support in a reactor, and water and tetraethylammonium hydroxide are added to the bottom of the reactor. Then the reaction is carried out at 400°C for 8 hours. After the reaction is completed, the obtained solid is washed with water and filtered for multiple times, and then dried at 120°C for 10 hours to obtain material A.

[0128] (2) Then, sodium hydroxide, aluminum nitrate, white carbon black, material A, and deionized water were added in the proportion (mass ratio of inorganic base, aluminum source, silicon source, material A, and water = 1.7:1.1:4:12:100) and mixed evenly. Then, the mixture was placed in a closed reactor and reacted at 200°C for 25 hours. After the reaction, the obtained solid sample was filtered several times, and then dried at 120°C for 10 hours to obtain material B.

[0129] (3) Then, ammonium nitrate and deionized water were added to material B in the ratio (mass ratio of ammonium nitrate, material B, and water = 16:15:100) and mixed evenly, followed by treatment at 85°C for 3 hours, and the treatment was repeated 3 times.

[0130] (4) The solid sample was filtered several times, dried at 120°C for 10 h, and finally calcined in air at 500°C for 10 h. The obtained sample was numbered C11.

[0131] The crystal structure of the prepared sample belongs to Y zeolite, which is a conventional form of Y zeolite.

[0132] Table 1 Physicochemical properties of samples obtained in various embodiments and comparative examples

[0133]

[0134] Note: The present invention uses the sample obtained in Example 1 as a reference, and its crystallinity is set to 100%. The relative crystallinity of all other samples is obtained by comparing with the crystallinity of the reference.

Claims

1. A hollow Y zeolite having the following characteristics: the zeolite crystal form is a Y zeolite structure, characterized by transmission electron microscopy as a single crystal particle with a hollow structure, and the center of the crystal is a cavity.

2. The hollow Y zeolite according to claim 1, characterized in that: The particle diameter of the hollow Y zeolite crystals is 80 to 650 nm, preferably 100 to 600 nm.

3. The hollow Y zeolite according to claim 1, characterized in that: The shell thickness of the hollow Y zeolite is 20 to 350 nm, preferably 30 to 300 nm.

4. The hollow Y zeolite according to claim 1, characterized in that: The specific surface area of ​​hollow Y zeolite is 280~730m 2 / g, preferably 300 to 700 m 2 / g; pore volume is 0.09~0.31cm 3 / g, preferably 0.1 to 0.3 cm 3 / g.

5. The hollow Y zeolite according to claim 1, characterized in that: The acid content of the hollow Y zeolite is 0.07 to 0.27 mmol / g, preferably 0.08 to 0.25 mmol / g.

6. The hollow Y zeolite according to claim 1, characterized in that: The oxide silicon-aluminum ratio of the hollow Y zeolite is 3 to 7, preferably 3.2 to 6.

5.

7. A method for synthesizing hollow Y zeolite, the method comprising the following steps: (1) treating Y zeolite in the presence of organic amine vapor, and after the treatment, washing, separating and drying to obtain material A; (2) The material A obtained in step (1), an inorganic base, an aluminum source, a silicon source and water are mixed uniformly, and after the reaction, the hollow NaY zeolite is obtained by washing, separating, drying and calcining.

8. A method for synthesizing hollow Y zeolite, the method comprising the following steps: (1) treating Y zeolite in the presence of organic amine vapor, and after the treatment, washing, separating and drying to obtain material A; (2) uniformly mixing the material A obtained in step (1), an inorganic base, an aluminum source, a silicon source, and water, and washing, separating, and drying after the reaction to obtain material B; (3) Material B is subjected to ammonium exchange treatment, and finally hollow HY zeolite is obtained after separation, drying and calcination.

9. The method for synthesizing hollow Y zeolite according to claim 7 or 8, characterized in that: The organic amine in step (1) is at least one of ethylenediamine, propylenediamine, butylenediamine, n-propylamine, isopropylamine, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide, preferably at least one of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide.

10. The method for synthesizing hollow Y zeolite according to claim 7 or 8, characterized in that: The treatment in step (1) is a gas-solid two-phase reaction, and the Y zeolite is treated in the presence of organic amine vapor; it is achieved in the following manner: a support is provided in the reactor, the Y zeolite is placed on the support, and a mixture of organic amine and water is added to the lower part of the reactor support; the Y zeolite is not in direct contact with the mixture of organic amine and water; the mass ratio of the Y zeolite, the organic amine, and the water is 8-25:8-25:100, preferably 10-20:10-20:

100.

11. The method for synthesizing hollow Y zeolite according to claim 7 or 8, characterized in that: The treatment temperature in step (1) is 280 to 530° C., preferably 300 to 500° C., and the treatment time is 5 to 12 h, preferably 6 to 10 h.

12. The method for synthesizing hollow Y zeolite according to claim 7 or 8, characterized in that: The drying conditions in step (1) are as follows: drying temperature is 100 to 140° C.; drying time is 5 to 15 hours.

13. The method for synthesizing hollow Y zeolite according to claim 7 or 8, characterized in that: The inorganic base in step (2) is one or more of sodium hydroxide, potassium hydroxide and lithium hydroxide.

14. The method for synthesizing hollow Y zeolite according to claim 7 or 8, characterized in that: The aluminum source in step (2) is one or more of sodium aluminate, aluminum sulfate, aluminum chloride, and aluminum nitrate.

15. The method for synthesizing hollow Y zeolite according to claim 7 or 8, characterized in that: The silicon source in step (2) is one or more of white carbon black, silica gel, and silica sol.

16. The method for synthesizing hollow Y zeolite according to claim 7 or 8, characterized in that: The mass ratio of inorganic base, aluminum source, silicon source, material A and water is 0.8-2.5:0.4-1.8:2.5-6:8-25:100, preferably 1-2: 0.5~1.5:3~5:10~20:100。 17. The method for synthesizing hollow Y zeolite according to claim 7 or 8, characterized in that: The reaction conditions in step (2) are as follows: the reaction temperature is 70 to 150° C., preferably 80 to 120° C., and the treatment time is 15 to 35 h, preferably 20 to 30 h.

18. The method for synthesizing hollow Y zeolite according to claim 7 or 8, characterized in that: The drying temperature in step (2) is 80 to 150° C., and the drying time is 1 to 20 hours.

19. The method for synthesizing hollow Y zeolite according to claim 7 or 8, characterized in that: The calcination temperature in step (2) is 400-700° C., and the calcination time is 1-20 hours; the calcination is carried out in air or oxygen atmosphere.

20. The method for synthesizing hollow Y zeolite according to claim 8, characterized in that: The ammonium exchange treatment in step (3) is to mix material B, ammonium salt and water for ion exchange treatment, wherein the mass ratio of material B, ammonium salt and water is 8-25:8-25:100, preferably 10-20:10-20:

100.

21. The method for synthesizing hollow Y zeolite according to claim 8, characterized in that: The ammonium salt is one or more of ammonium nitrate and ammonium chloride.

22. The method for synthesizing hollow Y zeolite according to claim 8, characterized in that: The ion exchange treatment temperature is 70 to 100° C., preferably 80 to 90° C., and the ion exchange treatment time is 1 to 5 h, preferably 2 to 4 h.

23. The method for synthesizing hollow Y zeolite according to claim 8, characterized in that: The drying temperature in step (3) is 80-150° C., and the drying time is 1-20 hours. The calcination temperature in step (3) is 400-600° C., and the calcination time is 1-10 hours. The calcination needs to be carried out in an oxygen-containing atmosphere.

24. A hollow Y zeolite obtained by the synthesis method according to any one of claims 7 to 23.

Citation Information

Patent Citations

  • Method for preparing hollow zeolite socony mobil-5 (ZSM-5) nanometer zeolite

    CN102491366A

  • Hollow beta zeolite and preparation method thereof

    CN104591220A

  • Composite molecular sieve, as well as preparation method and application thereof

    CN104549460A

  • Multi-stage structure molecular sieve hollow microsphere, preparation methods and application

    CN105271285A

  • Preparation method of hollow USY molecular sieve

    CN105712374A